Comprehensive design and analysis of a 300L steel fuel tank for heavy off-road vehicles: numerical and experimental insights - Verma, Aditya; Shankar, Ravi; Malik Shaik, Ameer; Veera Siva Reddy, B.; Chandrasekhara Sastry, C.; Shaik, Nizmi; Salunkhe, Sachin; Cep, Robert; Abouel Nasr, Emad (Frontiers in Mechanical Engineering, 2024)
The objective of this research paper is to provide a comprehensive understanding of the design and analysis of steel fuel tanks for high speed, off-road, ground vehicles and to highlight the critical points that must be considered while designing and constructing such fuel tanks. The tank has been analysed as per AIS 093, for internal pressure testing. Stability analysis for sloshing of liquid inside the tank and weldment analysis for the joints, to identify critical areas of crack generation along with fatigue life projection of critical welds. To verify a prototype tank manufactured, pressure tested, and deformation measured which was compared with FEM results. Tanks were designed by incorporating all safety parameters with respect to its functionality and structural rigidity with the help of relevant codes and standards.